Modeling pollutant discharges in a channel: Water quality control and treatment using carbon nanotubes for filtration and adsorption - Adeosun, Adeshina Taofeeq; Abdul Rahman, Mohd Kasim; Akolade, Mojeed Taiwo (Elsevier, 2025)
Clean water has been an essential commodity since the dawn of human existence, contributing immensely to well-being in both domestic and industrial contexts. However, pollutants like sewage, pesticides, and other contaminants are frequently introduced into water sources through accidental or negligent actions. To address these challenges, the study seeks to advance knowledge by theoretically enhancing water quality through the modeling of carbon nanotube suspension for filtration and adsorption purposes. The pollutant combines with the water in the channel to form a sludge is modeled under the fluid power-law rheology while filtration and adsorption rates where assumed concentration dependent. Carbon nanotubes are dispersed uniformly within the channel to function as a filter and adsorbent. The mass and momentum equations governing the problem are formulated and then solved using an efficient numerical scheme: the bivariate spectral local linearization method (BSLLM). The findings reveal that the presence of carbon nanotubes leads to a reduction in flow velocity while effectively decreasing pollutant concentration due to enhanced filtration and adsorption rates. It is also observed that continuous pollutant discharge increases water density, thereby inducing a higher flow rate. Conversely, the flow speed decreases due to the narrowing of the pore matrix caused by the presence of single-walled carbon nanotubes (SWCNTs). Additionally, the suction effect enhances the transverse removal of pollutants from the suction wall, thereby decreasing the concentration gradient at the wall.